Dual-Resonance U-Shaped Wearable Antenna with T-Slot Ground for On-Body Biomedical Devices - Abuelhaija, A.; Hamdan, M.; Saleh, G.; Salama, S.; Issa, S.; Nashwan, O.; Ashyap, A. (Advanced electromagnetics, 2025)
This study introduces a miniaturized and adaptable dual-band textile antenna, meticulously designed for implementation in wearable biomedical systems. It functions at 2.45 GHz and 5.8 GHz, covering the ISM (Industrial, Scientific, and Medical) frequency ranges. The antenna features a U-shaped patch with a T-shaped slotted ground plane, built from denim fabric (εr = 1.68) and ShieldIt Super conductive material. Following several design optimizations—such as via placement, curvature conformity, and slot tuning—the final prototype shows reliable impedance matching (S11 < -10 dB across both bands) and consistent radiation performance, validated using CST and COMSOL simulations. The antenna maintains dependable performance on the human body, with SAR levels staying within safe exposure thresholds (1.18 W/kg at 2.45 GHz and 1.44 W/kg at 5.8 GHz). Although radiation efficiency drops are observed when worn (approximately -10.5 dB and -15.6 dB at 2.45 GHz and 5.8 GHz respectively) due to body absorption, the radiation pattern remains directed and functional. These characteristics make the design well-suited for body-worn communication systems used in healthcare monitoring, fitness tracking, and military contexts. This flexible antenna meets safety and comfort requirements, offering a viable solution for WLAN/WBAN implementations in wearable technology.